Plant water stress, leaf temperature, and spider mite (Acari: Tetranychidae) outbreaks in California vineyards - Stavrinides, Menelaos; Daane, Kent M; Lampinen, Bruce D; Mills, Nicholas J. (My University, 2010)
We evaluated the relationships between plant water status and leaf temperature, and between leaf temperature and spider mite (Acari: Tetranychidae) and predatory mite (Acari: Phytoseiidae) populations in eight vineyards in California in 2006 and 2007. Temperature of south-facing leaves increased significantly by 0.8°C for every 1.0°C increase in ambient air temperature, and by 5.3°C for every one MPa drop in leaf water potential. Peak population densities of Pacific spider mite, Tetranychus pacificus McGregor, increased significantly with increasing frequency of leaf temperatures above 31°C. In contrast, peak population densities of Willamette spider mite, Eotetranychus willamettei (McGregor), showed no relationship with the frequency of leaf temperatures above 31°C. This differential relationship between the two mite species and high leaf temperatures is consistent with their upper thresholds for development, which are 40°C for T. pacificus and 31°C for E. willamettei, as identified in a previous study. Predatory mite population densities showed no relationship with peak population densities of either spider mite species during the analysis period, but decreased with the frequency of leaf temperatures above 31°C. In addition, predatory mite population densities were significantly higher on south-facing than interior leaves after adjusting for the effect of leaf temperature. These results help to explain why outbreaks of T. pacificus occur in warmer or water-stressed vineyards, whereas E. willamettei develops higher populations in cooler or well-irrigated vineyards. In addition, these results suggest that regulated deficit irrigation should be implemented with caution, especially in those vineyards with a high risk of T. pacificus outbreaks.
Keywords: grape plants; leaf temperature; plant water stress; predatory mites; spider mites